PERSEPSI MASYARAKAT TERHADAP PENGEMBANGAN DESA WISATA PELAGA SEBAGAI GREEN VILLAGE DESTINATION - A.A. Ayu Arun Suwi Arianty; I Made Trisna Semara; Ni Nyoman Nadya Pradnyandari (Jurnal Ilmiah Hospitality Management, 2018)
ABSTRACTThe aim of the study was to determine the community's perception of the development of Pelaga Tourism Village. This study uses a qualitative method which is a method that is descriptive in nature, and more displays the process of meaning. Data collection techniques using in-depth interview techniques with informants sourced from local communities. The results of his research stated that people's perception of the development of Pelaga Tourism Village was quite good. However, there are some public perceptions that stated that they were not yet optimistic, especially the impact of the development of Pelaga Tourism Village on social culture and the environment. Pelaga Tourism Village Development still has a lot of negative impacts.Â Keywords: tourism village, society, perception